UPAYA IRAN BERGABUNG DENGAN SHANGHAI COOPERATION ORGANISATION (SCO) - Pramudya Pratama; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Shanghai Cooperation Organisation (SCO) is a multilateral organization formed in 2001 by the People's Republic of China, Russia, Kazakhstan, Kyrgyzstan, and Tajikistan. At the beginning of its establishment the SCO aimed to solve the problem of national boundaries between SCO member states. In its development, SCO has entered other fields, such as economics, politics, culture and technology. SCO is a young organization that has extraordinary potential, especially in the economic field. Iran is a middle eastern country rich in its natural resources, especially oil and gas. In its development, Iran often experiences ups and downs in its economy, this is due to the many sanctions imposed by western countries, especially the United States. Therefore, Iran during the Ahmadinejad era initiated a policy of